2021
DOI: 10.1016/j.injury.2021.02.075
|View full text |Cite
|
Sign up to set email alerts
|

Associations of On-arrival Vital Signs with 24-hour In-hospital Mortality in Adult Trauma Patients Admitted to Four Public University Hospitals in Urban India: A Prospective Multi-Centre Cohort Study

Abstract: (SpO2 < 90%), Tachypnoea (RR > 20brpm) and severe (3-8) and moderate (9-12) GCS having strong association with 24-hour mortality. Notably, the patients with missing values for SBP, HR and RR also demonstrated higher odds of 24-hour mortality. The Injury Severity Scores (ISS) did not corelate with 24-hour mortality. Conclusion: The routinely measured GCS and vital signs including SBP, HR, SpO2 and RR are independently associated with 24-hour in-hospital mortality in the context of university hospitals of urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…RR is a readily available clinical indicator for early identification of high-risk patients after trauma, and shortness of breath correlates strongly with 24-h mortality [ 30 , 31 ]. This study confirmed that RR is a risk factor for death in patients with cervical spine fractures.…”
Section: Discussionmentioning
confidence: 99%
“…RR is a readily available clinical indicator for early identification of high-risk patients after trauma, and shortness of breath correlates strongly with 24-h mortality [ 30 , 31 ]. This study confirmed that RR is a risk factor for death in patients with cervical spine fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The other factor, overcrowding of the ED with limitation of resources, may also lead to inadequate trauma care. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Although the reasons for this undertriage are multifactorial, in this case, the lack of appropriate training or standard, uniform protocol for patient management in the ED to quickly identify these patients among those that have normal physiological parameters is most evident. The other factor, overcrowding of the ED with limitation of resources, may also lead to inadequate trauma care 25…”
Section: Discussionmentioning
confidence: 99%
“…The results of the statistical data's predictive power derived from the basic vital signs and simple demographic data such as age save the most resources and are the most useful. Vital signs were chosen as features mainly because most vital signs can be easily measured using non-invasive equipment, and vital signs are the most basic health indicators that are easily understood by all healthcare professionals [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%